Lactococcus lactis subsp. lactis isolated from fermented milk products and its antimicrobial potential. Issue 1 (1st January 2019) - Akbar, Ali; Sadiq, Muhammad Bilal; Ali, Imran; Anwar, Muhammad; Muhammad, Niaz; Muhammad, Javed; Shafee, Muhammad; Ullah, Sami; Gul, Zareen; Qasim, Said; Ahmad, Shaikh; Anal, Anil Kumar
ABSTRACT: The fermented milk samples (n = 25) were examined for the presence of lactic acid bacteria (LAB) with broad antimicrobial potential. Isolates were identified based on biochemical profiling. Antibacterial activity of the LAB was determined against Salmonella typhimurium, Staphylococcus aureus, Escherichia coli and Listeria monocytogenes . L. lactis subsp. lactis showed broad antimicrobial spectrum compared to other isolates and probiotic evaluation showed viability of L. lactis at low pH (3), 3% and 0.3% bile salts. Bacteriocin from the LAB isolate ( L. lactis subsp. lactis ) was partially purified by precipitation, dialysis and microfiltration followed by molecular weight determination. The partially purified bacteriocin was used for biopreservation of poultry meat against target bacteria ( S. aureus and S. typhimurium ). The antimicrobial metabolites were also found active against S. typhimurium (11.2 ± 1.72 mm) and E. coli (13.4 ± 1.15 mm). LAB reduced the number of target bacteria by 10-fold in milk after 24 h of incubation. Crude bacteriocin reduced the number of target bacteria in poultry meat, from initial count of 10 5 –10 6 CFU/g to 10 1 CFU/g for S. aureus and to 10 2 CFU/g for S. typhimurium respectively.